Robust speed control algorithm with disturbance observer for uncertain PMSM - Kim, Seok Kyoon; Lee, June Seok; Lee, Kyo Beum (International Journal of Electronics, 2018)
This article suggests a robust cascade speed control algorithm for a permanent magnet synchronous motor (PMSM) combining the classical feedback linearising (FL) method and the disturbance observers (DOBs) without the integrators. The contributions of this method are twofold. The first one is to provide the simple DOBs for not only guaranteeing the closed-loop performance recovery property but also removing the steady-state errors without the integrators with respect to the tracking errors. The second one is to prove that the inner and outer loops are stabilised by the proposed cascade-type controller, simultaneously. The simulation and experimental results reveal that the proposed method maintains the speed tracking performance to be satisfactory for a wide operating region with the fixed control gain despite a plant-model mismatch where a 3-kW interior PMSM is utilised.
Keywords: Cascade speed control; Classical feedback; Closed-loop performance; Disturbance observer; Performance recovery; Permanent Magnet Synchronous Motor; Plant model mismatches; Steady state errors; disturbance observer; performance recovery; robust control; Speed control algorithm